Analysis of Indonesia's Cooperation with China Through the Belt and Road Initiative (BRI) can Provide Opportunities or Challenges for Indonesia to Realize the World Maritime Axis - Gusriandari, Wahyu; Saputro, Guntur Eko; Sarjito, Aris; Rinaldi, M. (PT FORMOSA CENDEKIA GLOBAL, 2024)
The World Maritime Axis policy initiated by President Joko Widodo has become one of the government's main focuses in national development in collaboration with the Chinese government through the Belt and Road Initiative (BRI). But sometimes it is also necessary to have a strategy carried out by the government in stemming the threats that come to support the world maritime axis. This has the potential to cause various asymmetrical threats around the economic field and loss of sovereignty, Indonesia's entry into the debt abyss, and the entry of laborers from China to Indonesia which will reduce employment opportunities for indigenous people. The research method uses quantitative data. The basis for the state planning process needs to be carefully prepared. Given that defense is one form of a spectrum of uncertainty that can make a